Hypoxia promotes chemotherapy resistance by down-regulating SKA1 gene expression in human osteosarcoma. Issue 3 (4th March 2017) - Ma, Qiong; Zhang, Yinglong; Liu, Tao; Jiang, Kuo; Wen, Yanhua; Fan, Qingyu; Qiu, Xiuchun
ABSTRACT: Drug resistance has always been the main problem in osteosarcoma treatment, and hypoxia seems to be one of the many causes for drug resistance. Therefore, in this study, we investigated how hypoxia triggers chemotherapy resistance in osteosarcoma. We first screened hypoxia- and normoxia- cultured osteosarcoma cells in silico to identify the differentially expressed genes specifically related to drug resistance. This led to the identification of spindle and kinetochore associated complex subunit 1 (SKA1) as a probable gene of interest. SKA1 was further overexpressed by a lentiviral vector into an osteosarcoma cell line to study its role in chemoresistance. Our data revealed that SKA1 overexpression reduced the expression of some multidrug resistance genes, and enhanced the sensitivity of two common chemotherapeutic drugs used in osteosarcoma patients, epirubicin (EPI) and ifosfamide (IFO). In addition, we also confirmed the role of SKA1 in EPI drug sensitivity in vivo . Taken together, our study indicated that hypoxia mediated downregulation of SKA1 expression increased the chemotherapy resistance in human osteosarcoma cells.